2018
DOI: 10.31602/dl.v1i1.1499
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Pembelajaran Komik Terhadap Minat Belajar Kimia Siswa Pada Materi Koloid Di Kelas Xi Mia Man 1 Banjarmasin

Abstract: Penelitian ini dilaksanakan di MAN 1 Banjarmasin dengan tujuan untuk mengetahui ada tidaknya pengaruh media pembelajaran komik terhadap minat belajar kimia siswa pada materi koloid. Penelitian ini merupakan penelitian eksperimen semu (quasi-experimental research). Populasi pada penelitian ini adalah seluruh siswa kelas XI MIA di MAN 1 Banjarmasin yang terdiri dari 3 kelas yaitu kelas XI MIA 1, XI MIA 2, dan XI MIA 3. Sampel dalam penelitian ini yaitu kelas XI MIA 1 (kelas eksperimen) dan kelas XI MIA 2 (kelas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…This developed picture storybook can increasingly trigger the curiosity of students to find more understanding of a segment in modules because this book included some informative and real materials associated to cystitis prevalence and the data of total patients with cystitis in Tambelan Sampit and Kampung Dalam in Eastern Pontianak (Figure 2b). As indicated by Marlinasari, et al (2018), the student's curiosity appeared when they found attracting things surrounding them, then they would be inspiringly motivated to discover, explore and learn new things.…”
Section: The Results Of Expert Validator's Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This developed picture storybook can increasingly trigger the curiosity of students to find more understanding of a segment in modules because this book included some informative and real materials associated to cystitis prevalence and the data of total patients with cystitis in Tambelan Sampit and Kampung Dalam in Eastern Pontianak (Figure 2b). As indicated by Marlinasari, et al (2018), the student's curiosity appeared when they found attracting things surrounding them, then they would be inspiringly motivated to discover, explore and learn new things.…”
Section: The Results Of Expert Validator's Assessmentmentioning
confidence: 99%
“…This result meaningfully showed that this picture storybook can trigger curiosity, motivate and attract students. Marlinasari, et al (2018) stated that a print media accessible in storybooks should display attractive pictures, harmonic colors as well as a good feature in order to induce curiosity in students over the modules read. Besides that, story plots in a picture storybook arranged systematically according to daily incidents in life may also bring curiosity in students as if they experienced that events by themselves (Yatno, et al, 2015;Zain, et al, 2013).…”
Section: Student's Response To the Picture Storybookmentioning
confidence: 99%
“…box question [9], snakes and ladders [12], scrapbook [14], dartboard [16], crosswords [17], KOKAMI [18], UNO card [20], and comic [22].…”
Section: Process Skillsmentioning
confidence: 99%
“…Chemistry as one of the science subject at school requires approaches, techniques, strategies, and learning models that are specified by the characteristics of chemistry itself [8][9][10] [11][12] [13][14] [15][16] [17] [18][19] [20] [21] [22][23] [24] [25]. Mastery of the characteristics of the field of chemistry can only apply to chemistry teachers with sufficiently high teaching hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation